Cerebral Palsy Updates - Kuru Bektaşoğlu, Pinar (IntechOpen, 2023)
Cerebral palsy is a debilitating disease that affects the everyday life of patients and their caregivers. Understanding its pathophysiology, preventing avoidable factors, and effectively treating the disease with the most appropriate approach is paramount in the management of patients with cerebral palsy. This book presents up-to-date information about the etiology, pathophysiology, social aspects, and optimum care and treatment alternatives of this chronic condition.